Peningkatan Kualitas Jerami Padi MenggunakanTeknologi Amoniasi Fermentasi - Muhamad Amin; Sofyan Damrah Hasan; Oscar Yanuarianto; Mohammad Iqbal; I Wayan Karda (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2016)
An experiment with aim to study the effect of probiotics combination level and length of fermentation on qualityimprovement of rice straw had been conducted at the Laboratory of Nutrition and Feed of Animal HusbandryFaculty, Mataram University. The research was arranged in a Completely Randomized Design in factorialarrangement 3 x 3 with 3 replications. The first factor was the level of probiotics (0, 2 and 4%), the second factorwas the period of fermentation (2, 4 and 6 weeks).The variables measured were crude protein, crude fiber, NDF,ADF, cellulose, hemicellulose, lignin, and in vitro digestibility of dry matter and organic matter. Data wereanalyzed by analysis of variance and tested further by Duncan's Multiple Range Test. The result show thattreatments combination of the probiotics level and fermentation period did not affect (P>0.05) the chemicalcomposition and digestibility. The level of probiotics increased (P<0.05) the crude protein and in vitro dry matterdigestibility. Meanwhile, the lenght of fermentation increased the crude protein and in vitro digestibility of drymatter and organic matter, but decreased the crude fiber, NDF, ADF, cellulose, and hemicellulose of Amofer ricestraw.